Fundos de investimento imobiliário listados na BM&FBOVESPA: análise comparativa entre rendimentos reais e estimados - Minosso, Anariele Maria (2018)
Real Estate Investment Trust is an alternative of direct or indirect investment in financial assets related to real estate. It is an attractive option for the individual investor, since it requires less disbursement and has greater liquidity compared to the acquisition of a property for lease. However, before investing in a real estate fund it is recommended to read your prospectus, which should present the necessary information for decision making. This research aims to identify if the income obtained by the investors of the Real Estate Investment Trusts meet the estimated income. For this purpose, annual cash flow projected data were collected, in periods ranging from 2005 to 2027, and yields distributed monthly, ranging from 2009 to 2017, by 37 real estate funds listed on BM&FBOVESPA. These were obtained through prospectuses and monthly reports and profitability disclosed by the funds. To compare the yields, the relative variation (%) of the income was calculated in relation to the annual estimate. However, the viability of the projected investment was first verified through the Net Present Value and Internal Rate of Return methods. All calculations were performed in Microsoft Excel Software spreadsheets, and presented through graphs and tables. Based on the results obtained, it was verified that the XTED FII, in the office segment, achieved the highest average annual income above the estimate, equivalent to 29.43% of the total investment cost, corresponding to a relative variation of 212.47% above the projection. Among the funds with lower than expected income, the ATSA FII was the one that distributed the lowest average annual income, equal to 0.74%, relative to a variation of 95.74% below that proposed. By analyzing the segments, the highest income was for the university sector and the lowest for the retail sector. In this way, the segments considered most advantageous for the investment are those of offices and universities. And the less attractive are those of malls and retail. Generally, it is concluded that the Real Estate Investment Trusts are a good option to invest because, in the period under review, they earned an average annual income of 11.60% of the amount invested, which represents a distribution above the average estimates of 10.72% annual return to the quota holders.